2010
DOI: 10.3324/haematol.2010.028241
|View full text |Cite
|
Sign up to set email alerts
|

CD4-positive T-helper cell responses to the PASD1 protein in patients with diffuse large B-cell lymphoma

Abstract: BackgroundVaccine development targeting the novel immunogenic Per ARNT Sim Domain containing 1 (PASD1) cancer testis antigen represents an attractive therapeutic approach for the significant number of patients with diffuse large B-cell lymphoma who are refractory to conventional treatment. Since CD4-positive T helper cells have crucial roles in promoting and maintaining immune responses to tumor antigens, the presence of a CD4-positive T-helper immune response to the PASD1 antigen in patients with diffuse larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Critical role of TCD4 cells is approved in controlling tumor growth and protecting mice against class II MHC negative tumors. It was shown in a study that the transformation of the TCD4 cell-specific adapter of tumor induced virus FBL-3 (MuLV) can control tumor growth in an independent pathway of CTL 46 .On the other hand, the TCD4 cells have also lethal activity to assist host defense against tumors 50 . These cells also secrete cytokines to activate the executive cells of innate immune such as macrophages and NK cells 51 .…”
Section: Immune System Stimulation To Treat Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Critical role of TCD4 cells is approved in controlling tumor growth and protecting mice against class II MHC negative tumors. It was shown in a study that the transformation of the TCD4 cell-specific adapter of tumor induced virus FBL-3 (MuLV) can control tumor growth in an independent pathway of CTL 46 .On the other hand, the TCD4 cells have also lethal activity to assist host defense against tumors 50 . These cells also secrete cytokines to activate the executive cells of innate immune such as macrophages and NK cells 51 .…”
Section: Immune System Stimulation To Treat Cancermentioning
confidence: 99%
“…The potential of TCD4 generated colonies was subsequently evaluated in identifying the normal processed forms of protein by the tumor cells, therefore, the tumor cells used in this study were manipulated to express class II MHC on the surface. The results showed the ability of TCD4 colonies in reidentifying the antigenic peptides that were naturally processed by tumor cells and presented with class II MHC 46,50,[52][53][78][79][80] .…”
Section: The Role Of Epitopes In Vaccine Designmentioning
confidence: 99%
“…Peptide sequence Immunogenicity of ways such as stimulating production of antibodies. CD4 responses against PASD1 epitopes were investigated by Ait-Tahar et al [65] in patients with DLBCL. They showed that immunogenic PASD1 epitopes predicted to bind several class II DR beta 1 alleles were able to induce CD4 + T helper responses to PASD1-positive cells from patients with DLBCL.…”
Section: Name Of Epitope Mhc Bindingmentioning
confidence: 99%
“…Further epitopes could be identified through the immunoscreening short overlapping peptide libraries [76,77] although some of the already predicted PASD1 epitopes [63][64][65] remain to be more thoroughly studied in vivo.…”
Section: Development Of Immunotherapy Strategies Targeting Pasd1mentioning
confidence: 99%
“…However, this approach has not been effective in clinical trials, probably due to lack of other effector T cells, such as T helper (Th) and memory cells (2) (2). Also, Th cells have a lethal function that helps the host defense system overcome tumor progression (5). Also, these cells prompt executive innate immune cells such as macrophages and NK cells through cytokine secretion (6).…”
Section: Introductionmentioning
confidence: 99%